A computational study of aortic insufficiency in patients supported with continuous flow left ventricular assist devices: Is it time for a paradigm shift in management? - Grinstein, Jonathan; Blanco, Pablo J.; Bulant, Carlos A.; Torii, Ryo; Bourantas, Christos V.; Lemos, Pedro A.; Garcia-Garcia, Hector M. (Frontiers in Cardiovascular Medicine, 2022)
Background: Traditional management of aortic inefficiency (AI) in LVAD patients utilizes speed augmentation (SA) to overcome regurgitant flow (RF) to augment net forward flow, but this strategy may predispose the patient to progressive valve pathology and right ventricular (RV) dysfunction. Methods: We employed a mathematical closed-loop model of the cardiovascular system in a patient supported by an LVAD. The impact of SA and pharmacological treatment on systemic and pulmonary vasculature were investigated in scenarios with varying degrees of RV to PA coupling and AI. Results: Severe AI reduced net flow from 5.4 L/min to 2.1 L/min in the coupled RV. SA led to a 42% increase in net flow and a 16% increase in RF with a decrease of 1.6% in RV myocardial oxygen consumption (MVO2). Blood pressure (BP) control with the coupled RV led to an 81% increase in net flow 15% reduction of RF and 8% reduction in RV MVO2. With an uncoupled RV, severe AI reduced net flow from 5.0 L/min to 1.8 L/min. SA increased net flow by 45%, RF by 15% and reduced RV MVO2 by 1.1%. BP control led to a 22% increase in net flow, 4.2% reduction in RF and 3.9% reduction in RV MVO2; pulmonary vasodilation led to a 18% increase in net flow, 7% reduction in RF and 26% reduction in RV MVO2; whereas combined BP control and pulmonary vasodilation led to a 113% increase in net flow, 20% reduction in RF and 31% reduction in RV MVO2. Conclusions: BP control and pulmonary vasodilation, particularly with an uncoupled RV can improve net flow with more advantageous effects on the RV and RF compared to speed augmentation.